MANAJEMEN KONFLIK KEAGAMAAN: Kearifan Lokal Dalam Upaya Resolusi Konflik Keagamaan di Sumatera Barat - Marpuah Marpuah (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Today, the life of the Indonesian people faces serious threats associated with the strength of social conflicts,bothvertically and horizontally. Indeed, the conflict seizes social, economical, political and cultural freedoms. Thisstudy used a qualitative approach by using interview, observation and documentation. Sources of Data were theRegional Office of MORA, KUB, FKUB, Kesbangpol Linmas, High Court, LKAAM and Bundo Kanduang.Data were analysed by descriptive and qualitative techniques. The results showed that in general the religiousconflicts in West Sumatra are not much surface. This is due to the high sense of tolerance and inter-religiousharmony in society. In the event of any religious conflicts and problems in the community, then all the relevantstakeholders such as Local Government, FKUB, Tungku Tigo Sajarangan and all devices, right down to forma special team and make consensus to resolve the conflict.